(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the scientific justification for a program aimed at forming the health-preserving competence of future physical education teachers in the process of professional training. The relevance of the study is due to the growing need to prepare pedagogical professionals capable of effectively implementing health-preserving technologies in the educational process, fostering a culture of a healthy lifestyle among students, and promoting improvements in their physical activity levels. The aim of the study is to provide a scientific rationale for a program that forms the health-preserving competence of future physical education teachers based on modern methodological approaches, enhancing the effectiveness of professional training and fostering a stable motivation for a healthy lifestyle in pedagogical practice. The research methods used include theoretical analysis of scientific and methodological literature, practical sources, and regulatory documents; pedagogical observations and experiments; sociological research methods; and mathematical analysis. The study involved 38 undergraduate students specializing in 014.11 Secondary Education (Physical Education) at Bohdan Khmelnytsky Melitopol State Pedagogical University. The proposed program is based on a comprehensive approach that integrates theoretical knowledge, practical skills, and motivational factors. It addresses several key objectives, including improving students’ physical fitness, fostering psycho-emotional resilience, developing self-regulation skills, maintaining emotional balance, enhancing social integration, and professional communication. The program is implemented in three main stages: preparatory, main, and control-reflective, ensuring its systematic, step-by-step, and effective execution. Key components of health-preserving competence are identified: axiological, motivational, informational-cognitive, psychophysiological, physical-health-oriented, cultural, and communicative. Special attention is given to individualized learning, considering students’ physical capabilities and personal characteristics. The research findings confirm that the proposed program contributes to the comprehensive development of professional competencies in future physical education teachers, increases their motivation for a healthy lifestyle, and facilitates the integration of innovative technologies into the educational process. The implementation of this program will aid in the preparation of competitive professionals capable of effectively applying health-preserving strategies in their pedagogical activities.